2022
DOI: 10.1088/1755-1315/1068/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Features of physico-chemical parameters of local varieties of lentil grains in Uzbekistan

Abstract: In Uzbekistan, special attention is paid to the cultivation of lentils and such types of grain are characterized by high quality indicators and physicochemical characteristics. In Uzbekistan, special attention is paid to the cultivation of lentils. Such types of grain are characterized by high quality indicators and physicochemical characteristics. The physico-chemical parameters of local varieties of lentil grains were studied. The technological characteristics of lentil grains were established, the distincti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Protein is a major component in alfalfa, as evidenced by the absorption peak near 3280 cm −1 representing N-H stretching vibrations and the involvement of O-H stretching vibrations from polysaccharides [51]. The typical protein bands centered around 1632 cm −1 , 1545 cm −1 , and 1400 cm −1 correspond to amide I and amide II groups, reflecting C=O stretching vibrations due to out-of-plane C-N stretching vibrations and N-H bonding/C-H stretching within proteins [52][53][54]. These peaks confirm that alfalfa is rich in protein and carbohydrates, which are essential for its quality.…”
Section: Infrared Spectroscopic Analysismentioning
confidence: 99%
“…Protein is a major component in alfalfa, as evidenced by the absorption peak near 3280 cm −1 representing N-H stretching vibrations and the involvement of O-H stretching vibrations from polysaccharides [51]. The typical protein bands centered around 1632 cm −1 , 1545 cm −1 , and 1400 cm −1 correspond to amide I and amide II groups, reflecting C=O stretching vibrations due to out-of-plane C-N stretching vibrations and N-H bonding/C-H stretching within proteins [52][53][54]. These peaks confirm that alfalfa is rich in protein and carbohydrates, which are essential for its quality.…”
Section: Infrared Spectroscopic Analysismentioning
confidence: 99%
“…Podder et al (2021) reported on the potentiality of lentil in providing Fe and Zn requirement to satisfy a major portion of the recommended Fe and Zn dietary allowances (RDAs) in deficient populations. Lentil protein isolates have various functional properties allowing their use as emulsifier and foaming agent (Khamidova et al, 2022). Moreover, lentil flours and fractions significantly improve the ability of food systems to retain water and fat.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lentil flours and fractions significantly improve the ability of food systems to retain water and fat. It is noteworthy that, even with extensive processing, lentil grain proteins retain their native conformation (Khamidova et al, 2022). Besides a variety of nutritional benefits, Patterson et al (2017) noted that lentils contain some antinutritional factors (ANFs) including lectins, trypsin enzyme inhibitors, phytates, saponins, and flatulence‐causing oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%